Ultrastructure of Middle Devonian Spores from New York State. - Gullickson, Kari (My University, 2009)
An assemblage of fossil plant spores from the Middle Devonian of New York state (approx. 375,000,000 years old) was extracted using standard palynological techniques. Little is known of the fine structure of spores of this geologic age since none have been examined with the TEM. Any information gathered will ultimately contribute to the understanding of plant diversity in this time of active plant evolution.
Ultrastructure of Spiny Megaspores from the Middle Devonian of New York State.
Color poster with text and images (Spring 2009)
Keywords: Plant spores, Fossil--Morphology; Plant spores, Fossil--New York (State); Paleobotany--Devonian; Posters